2014
DOI: 10.1021/ie4036737
|View full text |Cite
|
Sign up to set email alerts
|

Methane Hydrate Formation and Thermal Based Dissociation Behavior in Silica Glass Bead Porous Media

Abstract: Formation and thermal based dissociation of methane pore space hydrate has been studied at various initial hydrate saturations and heating rates utilizing a 1.3 cm 3 glass bead sample pack. Initial hydrate formation occurred rapidly after pressurization and proceeded at a higher rate for systems with the lower initial water saturation. Peak initial formation rates for 21%, 41%, and 60% initial water saturation was 4.3 × 10 −6 , 1.44 × 10 −6 , and 1.7 × 10 −6 mol/s, respectively. Three distinct stages of format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 24 publications
4
35
0
2
Order By: Relevance
“…During the experiment with the huff and puff in conjunction with the depressurization method, their results also show that the value of energy efficiency ranges from 15.6 to 41 at the steady process of gas production, which is lower than our results due to the high temperature of injection water (130°C). Therefore, the injection water with high temperature would yield higher rate of gas production; however, more energy would be consumed by the sensible heat of porous media, which would decrease the energy efficiency [21,28,38,39,67]. The results of the combined method show an obvious advantage in the energy efficiency, especially for the highly saturated hydrate-bearing sediments [21,28,38].…”
Section: The Gas Production At Different Hydrate Saturations Using Thmentioning
confidence: 99%
See 2 more Smart Citations
“…During the experiment with the huff and puff in conjunction with the depressurization method, their results also show that the value of energy efficiency ranges from 15.6 to 41 at the steady process of gas production, which is lower than our results due to the high temperature of injection water (130°C). Therefore, the injection water with high temperature would yield higher rate of gas production; however, more energy would be consumed by the sensible heat of porous media, which would decrease the energy efficiency [21,28,38,39,67]. The results of the combined method show an obvious advantage in the energy efficiency, especially for the highly saturated hydrate-bearing sediments [21,28,38].…”
Section: The Gas Production At Different Hydrate Saturations Using Thmentioning
confidence: 99%
“…Therefore, the injection water with high temperature would yield higher rate of gas production; however, more energy would be consumed by the sensible heat of porous media, which would decrease the energy efficiency [21,28,38,39,67]. The results of the combined method show an obvious advantage in the energy efficiency, especially for the highly saturated hydrate-bearing sediments [21,28,38]. Compared with the warm-water injection method (Run 4-6), the energy efficiency for the combined method (Run 7-9) had increments of 13.32, 23.09 and 28.38, for S hi of 31.9%, 41.31% and 51.61%, respectively.…”
Section: The Gas Production At Different Hydrate Saturations Using Thmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important characteristic of the sea water is the water temperature that its effects are very high on the physical and chemical changes in the sea water (Fitzgerald et al 2014).…”
Section: Gas Hydrates As a Potential Future Energy Resourcementioning
confidence: 99%
“…The water content of the sediments was found to have a significant impact on the formation behaviors of gas hydrates. Fitzgerald et al [16] studied the formation behaviors of methane hydrate in the pore space of glass beads at various water saturations. They observed that the hydrate formation displays multistage formation behavior and the hydrate growth rate is higher for systems with the lower initial water saturation.…”
Section: Introductionmentioning
confidence: 99%